DEVELOPING A GENRE-BASED ACADEMIC WRITING MODULE FOR ENGLISH DEPARTMENT STUDENTS - Sitompul, Siti Kholija; Mukminatien, Nur; Ivone, Francisca Maria (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2025)
English department students studying English as a Foreign Language (EFL) in Indonesia often struggle to build some core academic writing skills, notably their ability to generate ideas and to think critically. Motivated by this, the study attempted to develop an academic writing module for English department students based on the Genre-Based Approach (GBA) that can assist them in focusing on the process of developing ideas for academic writing as well as applying critical thinking when writing academic essays. Borg and Gall’s (1983) six-stage Research and Development (RD) model was employed. The developed module, which adhered to the GBA framework, includes four learning stages, i.e., (1) Building Knowledge of the Field, (2) Modelling of the Text, (3) Joint Construction of the Text, and (4) Independent Construction of the Text, as well as various tasks that allow language learners to generate ideas and construct sentences appropriate for academic writing. In addition, the module contains writing theories, tasks, and strategies for building some core academic writing skills. During its development, the module was refined based on recommendations from academic writing and Systemic Functional Linguistics (SFL) experts. Following that, a small-scale try-out was conducted with eleven English department students. The trial revealed that the target users perceived the module as beneficial for developing basic academic writing skills, as it systematically guided them through the writing process with the support of tasks, lecturers, and peers.